Prognostic role of the lymphocyte-to-monocyte ratio in colorectal cancer: An up-to-date meta-analysis - Wu, Qingbin (Medicine (Baltimore), 2017)
BACKGROUND: Although previous meta-analyses have proved that lymphocyte-to-monocyte ratio (LMR) is a prognostic factor in solid cancers, its prognostic role in colorectal cancer (CRC) remains controversial. We, therefore, conducted this up-to-date meta-analysis to evaluate the prognostic role of the LMR in CRC. METHODS: A systematic search was performed in PubMed and Embase for relevant studies in November 2016. Article assessing the prognostic role of LMR in CRC was enrolled in this meta-analysis. Data and characteristics of each study were extracted. A meta-analysis was performed to generate pooled hazard ratio (HR) and 95% confidence intervals (95% CIs) for overall survival (OS) and disease-free survival. Begg funnel plot was used to evaluate publication bias. RESULTS: Eleven studies published between 2014 and 2016 with a total of 9045 patients were enrolled in this meta-analysis. Our findings indicated that a low LMR predicted a worse OS (HR 1.57, 95% CI 1.30–1.90, P < .001) and disease-free survival. (HR 1.25, 95% CI 1.13–1.39, P < .001) for patients with CRC. Subgroup analyses according to stage (I–III and IV) and LMR cut-off value (<3.00 and ≥3.00) showed a significant prognostic value of LMR on OS. Begg funnel plot showed that publication bias existed in this meta-analysis. CONCLUSIONS: This up-to-date meta-analysis shows that a low LMR is associated with poor survival in patients with CRC, although the publication bias is existed. Large-sample multicenter prospective cohort is needed to assess the role of the LMR in CRC patients.